2013
DOI: 10.1128/iai.00392-13
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Chaperone Hfq Promotes Fitness of Actinobacillus pleuropneumoniae during Porcine Pleuropneumonia

Abstract: Actinobacillus pleuropneumoniae is the etiological agent of porcine pleuropneumonia, an economically important disease of pigs. The hfq gene in A. pleuropneumoniae, encoding the RNA chaperone and posttranscriptional regulator Hfq, is upregulated during infection of porcine lungs. To investigate the role of this in vivo-induced gene in A. pleuropneumoniae, an hfq mutant strain was constructed. The hfq mutant was defective in biofilm formation on abiotic surfaces. The level of pgaC transcript, encoding the biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 53 publications
2
30
1
Order By: Relevance
“…Although the relevance of sRNAs in A. pleuropneumoniae pathogenesis is suggested by previous work with mutants for the sRNA molecular chaperone Hfq (Subashchandrabose et al 2013;Pereira et al 2015b), little information exists on abundance and possible roles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the relevance of sRNAs in A. pleuropneumoniae pathogenesis is suggested by previous work with mutants for the sRNA molecular chaperone Hfq (Subashchandrabose et al 2013;Pereira et al 2015b), little information exists on abundance and possible roles.…”
Section: Discussionmentioning
confidence: 99%
“…We envisage that the Arccs discovered in our study are negative regulators, although further experiments, e.g., comparative RNA-seq Most sRNAs have as targets mRNAs directly implicated in either virulence or stress resistance. Although this was partially expected given the aforementioned phenotypes of reduced biofilm-forming capacity, sensitivity to oxidative stress (Subashchandrabose et al 2013), and reduced virulence in an alternative infection model (Pereira et al 2015b) displayed by A. pleuropneumoniae mutants for the hfq gene, new candidates for virulence determinants were defined by the present regulatory network. Two categories of potential targets that are part of extremely important systems for the establishment of A. pleuropneumoniae as a pig pathogen, and thus strong mutant candidates for live attenuated vaccines, are the iron-acquisition systems and Apx toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this normal in vitro growth rate, competition assays in mice revealed that the P. multocida hfq mutant showed significantly reduced fitness in vivo. Reduced in vivo fitness has also been demonstrated for hfq mutant strains of Y. pestis, Klebsiella pneumoniae, Francisella tularensis, and Actinobacillus pleuropneumoniae (20,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 96%
“…Hfq of Escherichia coli is a protein of 102 aa residues, and its orthologs exist in a number of Gram-negative and -positive bacteria constituting the Hfq family of proteins (14)(15)(16)(17). Hfq has been shown to play a role in the virulence of uropathogenic E. coli (18) and other bacterial species (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). However, the mechanism involved in Hfq-mediated changes in the virulence of bacteria remains unclear.…”
mentioning
confidence: 99%